Gender and female reproductive communication in Ugep, Nigeria (2010)
Gender affects the communication of female reproductive matters in Ugep. Biological and cultural determinism of gender stratification theories help explain this sex-based interaction. The funtionalist suggest that familes are organised among instrumental-expressive lines, with men specializing in instrumental tasks and women in expressive ones. Accondingly, the study reveals tha mother play a greater roles in the communication of female sexual and reproductive health matters. They are evaluated better communicators, more frequent communicators and with less negative styles of communication. This finding shows a gendered communication struture where there exist very little discussions among fathers and daughters. Rather than sexuality communication, fathers' conversation focused on education, carrier aspiration, chid discipline and material provision. mothers were thus identified as playing the major expressive role in female communication. Gender- role attitude is therfore significantly associated with reproductive communication in the family.